The Effect of Perceived Usefulness, Perceived Ease of Use and Perceived Price on Customer Loyalty in Gojek Through Customer Satisfaction (Study on Gojek Apps Users in Jabodetabek) - Glen Meyer Suryatenggara; Kandi Sofia Senastri Dahlan (Journal of Business & Applied Management, 2022)
This research is based on the competition in the online transportation service sector between Gojek and several other companies developing in Indonesia recent years like Grab and others. The increasing number of internet users affect the increasing number of online transportation users. The purpose of this research is proving the effect of Perceived Usefulness, Perceived Ease of Use, Perceived Price on Customer Loyalty in Gojek through Customer Satisfaction. The Technology Acceptance Model (TAM Model) is the theory used in this research. TAM Model has key variables such as Perceived Usefulness and Perceived Ease of Use which are used to measure user’s confidence in the level of utility and level of ease of using technology. In addition, price is also a consideration for customer in using online transportation services. This research is conducted quantitatively using Structural Equation Modeling (SEM). Smart PLS 3.0 is software used for analyzing data in this research. The data in this study will be obtained through questionnaires distributed to users of online transportation service (Gojek) in Jabodetabek (Jakarta-Bogor-Depok-Tangerang-Bekasi). The number of respondents collected in this research are 255 respondents. Results of this research are Perceived Usefulness, Perceived Ease of Use and Perceived Price affect Customer Satisfaction positively and significantly. On other hand, Perceived Usefulness, Perceived Ease of Use and Perceived Price affect Customer Loyalty through Customer Satisfaction positively and significantly. Other Criteria of Service Quality like Perceived Safety, Perceived Risk and Responsiveness should be tested in the future research. Besides that, more specific segment of population and other method such as quantitative & interview method should be done in the future research.